Virtual library exhibition activity in the system of scientific communications - Koval Tatiana; Turovska Lesia (Bìblìotečnij vìsnik, 2022)

(untitled)
The object of research is the library as an integrative information and communication center. The subject of research is a virtual library exhibition activity. The purpose of the study is to highlight the features of the virtual exhibition activities of the scientific library and substantiate the effectiveness of the organization and promotionof electronic library exhibitions in the system of scientific communications. Realization of the purpose provides generalization of experience of the V. I. Vernadskyі National Library of Ukraine on an example of one of its leading divisions - Department of complex library service. Methodological basis of the study - system, information, structural and functional, comparative, historical, terminological approaches, as well as a set of general scientific, specific scientific and special methods. The scientific novelty is the expansion of ideas about the virtual exhibition activities ofthe scientific library with the involvement of developments in the field of library science, as well as in the field of social communication theory, sociology, statistics, social psychology, library management; developing a palette of practical approaches to the use of library tools of scientific communication in the process of meeting the needs of remote users. Conclusions. Expanding its activities in the virtual information space, the library provides optimal development of users of this space, attracts its own means of scientific communication in everyday practice, creates the best conditions for unlimited use of different professional categories and groups. Thus, the library becomes a center of integrative information and communication support of scientific, educational, industrial, cultural, educational and other social processes, and the set of library means of scientific communication - a key vector of its innovative development. Perspectives. The results of the study initiate the development of further strategy of the modern scientific library; construction of radically new dialogic forms of communication with the user (physical and remote) in the system ofscientific communications.